2017
DOI: 10.1021/acsnano.7b05856
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Few-Layer Manganese Thiophosphite

Abstract: This work reports an experimental study on an antiferromagnetic honeycomb lattice of MnPS that couples the valley degree of freedom to a macroscopic antiferromagnetic order. The crystal structure of MnPS is identified by high-resolution scanning transmission electron microscopy. Layer-dependent angle-resolved polarized Raman fingerprints of the MnPS crystal are obtained, and the Raman peak at 383 cm exhibits 100% polarity. Temperature dependences of anisotropic magnetic susceptibility of the MnPS crystal are m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 62 publications
4
70
0
3
Order By: Relevance
“…124,125,128,130,134,135 Raman spectroscopy provided the first evidence for a long-range magnetic order in atomically thin MPX 3 . [124][125][126][127]135,136 Monolayer FePS 3 has, for instance, been successfully exfoliated from its bulk and shown Raman features due to Brillouin zone folding arising from antiferromagnetic ordering below its transition temperature. 124,125 The magnetic transition temperature remains almost independent or weakly dependent on the thickness from bulk to the monolayer limit at 118 K 124 or 104 K. 125 This indicates intralayer spin arrangement dominating the magnetic structure in the monolayer sample.…”
Section: D-vdw Antiferromagnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…124,125,128,130,134,135 Raman spectroscopy provided the first evidence for a long-range magnetic order in atomically thin MPX 3 . [124][125][126][127]135,136 Monolayer FePS 3 has, for instance, been successfully exfoliated from its bulk and shown Raman features due to Brillouin zone folding arising from antiferromagnetic ordering below its transition temperature. 124,125 The magnetic transition temperature remains almost independent or weakly dependent on the thickness from bulk to the monolayer limit at 118 K 124 or 104 K. 125 This indicates intralayer spin arrangement dominating the magnetic structure in the monolayer sample.…”
Section: D-vdw Antiferromagnetsmentioning
confidence: 99%
“…We anticipate more works to appear for NiPS 3 and other members of MPX 3 . 126,127,131,[136][137][138][139][140][141] For instance, recent studies have shown exciting possibilities of making field-effect transistors, 136,142 tunneling devices, 143 and photodetectors, 135,144 using MPX 3 . Furthermore, some MPX 3 nanosheets have been predicted to become ferromagnetic semimetals depending on charge carrier doping.…”
Section: D-vdw Antiferromagnetsmentioning
confidence: 99%
“…[36,63,64] Als Te ndenz zeigten Studien an MPCh n -Volumenkristallen, dass fürM PSe 3 das Onset-Potential bei À10 mA cm À2 generell geringer war als fürM PS 3 . [36,63,64] Als Te ndenz zeigten Studien an MPCh n -Volumenkristallen, dass fürM PSe 3 das Onset-Potential bei À10 mA cm À2 generell geringer war als fürM PS 3 .…”
Section: Elektrochemische Energieumwandlungunclassified
“…Hier verspricht die Klebebandmethode ("Scotch tape method") die beste Qualitätv on großen, aus einer Einzelschicht oder aus wenigen Schichten bestehenden Flocken. [20,[35][36][37][38][39] Diese exfolierten Materialien eignen sich hervorragend fürdie grundlegende Erforschung physikalischer Eigenschaften, die jeweiligen Herstellungsverfahren sind jedoch nur sehr begrenzt skalierbar.D as Kugelmahlen und die Exfoliation in der Flüssigphase,d.h.inLçsungsmitteln wie NMP und DMF,s ind bekannte Methoden fürd ie Exfoliation im Großmaßstab, [40][41][42][43][44][45][46][47] führen aber gewçhnlich zu einem hçheren Anteil an Verunreinigungen und Defekten. Fürp hotoelektronische Anwendungen ist dies zwar nicht ideal, bei guter Kontrolle kçnnen exfolierte MPCh 3 -Materialien als elektro-Abbildung 1. a) Relevante Elemente der MPCh 3 -Verbindungen fürEnergieanwendungen sind im Periodensystem hervorgehoben.…”
Section: Synthese Interkalation Und Exfoliationunclassified
See 1 more Smart Citation